2022
DOI: 10.1038/s41598-022-20329-x
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-fast green microwave assisted synthesis of NaFePO4-C nanocomposites for sodium ion batteries and supercapacitors

Abstract: Sodium ion batteries are favored in stationary and large scale power storage due to their low cost and nontoxicity. As the lithium is replaced with sodium due to the cost motive, a cheap processing method is needed to maintain the cell price as low as possible. We report an ultra-fast synthesis method that utilizes the high microwave absorbance of silicon carbide content in rice straw ash. Amorphous/maricite mixtures of sodium iron phosphates-carbon composites (NaFePO4-C) are synthesized, crystallized, and car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…A slight weight increase at 400–500 °C was ascribed to the oxidation of Fe 2+ species in the samples. , The Raman spectra illustrates that the intensity ratio of I D / I G for several samples is similar and calculated to be ∼1.04 (Figure S3), indicating the main amorphous state of the carbon framework due to low calcination temperature during the sample synthesis process . By comparing the Fourier transform infrared (FT-IR) spectra between NFP and NFPP-4 samples (Figure S4), it could be found that the stretching modes of the PO 4 group (∼1000 cm –1 ) and the vibration bonds of Fe–O (∼500 cm –1 ) have visible difference due to intrinsic structure diversities. , As a contrast, the NFPP-4.5 sample shows the structure and group features from both NFP and NFPP-4, which is in good agreement with the XRD analysis. Figures f and S5 exhibit the representative scanning electron microscopy (SEM) images of samples, which confirms the irregular micron-sized particle morphology.…”
Section: Results and Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…A slight weight increase at 400–500 °C was ascribed to the oxidation of Fe 2+ species in the samples. , The Raman spectra illustrates that the intensity ratio of I D / I G for several samples is similar and calculated to be ∼1.04 (Figure S3), indicating the main amorphous state of the carbon framework due to low calcination temperature during the sample synthesis process . By comparing the Fourier transform infrared (FT-IR) spectra between NFP and NFPP-4 samples (Figure S4), it could be found that the stretching modes of the PO 4 group (∼1000 cm –1 ) and the vibration bonds of Fe–O (∼500 cm –1 ) have visible difference due to intrinsic structure diversities. , As a contrast, the NFPP-4.5 sample shows the structure and group features from both NFP and NFPP-4, which is in good agreement with the XRD analysis. Figures f and S5 exhibit the representative scanning electron microscopy (SEM) images of samples, which confirms the irregular micron-sized particle morphology.…”
Section: Results and Discussionmentioning
confidence: 86%
“…Figure i compares the Raman spectra of several samples, which could reflect the subtle details of Fe–O bonds in the structure framework. The strong peaks between 200 and 300 cm –1 correspond to the FeO 6 by bridge sharing in maricite-type NFP phase. , The broadening and lowering of peak reflection in the NFPP-4 could be ascribed to the connecting patterns of FeO 6 or FeO 5 polyhedron in a different corner sharing way . Obviously, the as-prepared NFPP-4.5 sample shows characteristics of both NFP and NFPP-4 due to its heterostructure.…”
Section: Results and Discussionmentioning
confidence: 93%
“…Fortunately, sodium exhibits chemical and physical properties very close to lithium and is abundant and evenly distributed in the Earth's crust. [20][21][22] Inspired by the successful application of olivine-type LFP in lithium-ion batteries, olivine NaFePO 4 (NFP) in sodium-ion batteries has received great attention, which has a notable theoretical capacity of 154 mAh g −1 and possesses a high redox potential. [23,24] However, olivine NFP cannot be synthesized using traditional high-temperature solid phase methods because the olivine phase converts to maricite phase at temperatures above 480 °C, [25,26] and olivine-type is generally prepared by ion exchange of olivine LFP.…”
Section: Introductionmentioning
confidence: 99%